On approximating any regular polygon by folding paper strips - Lazo, Fernando A. (Animo Repository, 1993)
There exists a Euclidean construction of a regular N-gon for very few values of N, and even for these N, we do not know in all cases the explicit constructions.This thesis is an exposition of a better alternative to the Euclidean construction of the regular N-gon. It shows how to construct an approximation, to any desired degree of accuracy, a regular N-gon for any value of N. Explicity and uncomplicated constructions involving only the folding of a straight strip of paper are described and the corresponding mathematical theory is discussed. In the process, an interesting interplay of geometry, analysis and number theory is illustrated.